Pengaruh Efektivitas Iklan dan Kepercayaan Merek terhadap Keputusan Pembelian Produk Lemonilo - Yovianty, Livia; Erdiansyah, Rezi; Aulia, Sisca (Prologia, 2022)
This research was conducted to obtain information about the effect of advertising effectiveness and brand trust on the purchasing decisions of Lemonilo products. In this study, researchers used a quantitative approach with a survei method. The sample of this study amounted to 110 people using primary data. The primary data comes from a questionnaire. The researcher used the validity test and the reliability test to test the instrument. In this study using multiple linear regression, t test, f test and test the coefficient of determination as a hypothesis test. The analysis of the results of this study is that the variables of advertising effectiveness and brand trust have an effect on purchasing decisions. The effectiveness of advertising depends on various conditions, one of which is whether the message conveyed is remembered by consumers, whether the message can be embedded in the minds of consumers, and whether consumers will buy it. Based on the coefficient of determination test, it can be seen that the dependent variable of purchasing decisions can be explained by the independent variables of advertising effectiveness and brand trust of 29.4%, while the remaining 70.6% is explained by other factors outside the study such as price to product quality.   Penelitian ini dilakukan untuk memperoleh informasi mengenai pengaruh efektivitas iklan dan kepercayaan merek terhadap keputusan pembelian produk Lemonilo. Pada penelitian ini peneliti menggunakan pendekatan kuantitatif dengan metode survei. Sampel penelitian ini berjumlah 110 orang dengan menggunakana data primer. Data primer tersebut berasal dari kuesioner. Peneliti menggunakan uji validitas dan uji realibilitas untuk uji instrumen. Dalam penelitian ini menggunakan regresi linier berganda, uji t, uji f, dan uji koefisien determinasi sebagai uji hipotesis. Analisis hasil penelitian tersebut adalah variabel efektivias iklan dan kepercayaan merek berpengaruh terhadap keputusan pembelian. Efektivitas iklan tergantung pada berbagai kondisi, salah satunya apakah pesan yang disampaikan diingat konsumen, apakah pesan dapat tertanam di benak konsumen, dan apakah konsumen akan membelinya. Berdasarkan uji koefisien determinasi terlihat variabel dependen keputusan pembelian dapat dijelaskan oleh variabel independen efektivitas iklan dan kepercayaan merek sebesar 29,4%, sedangkan sisanya sebesar 70,6% dijelaskan oleh faktor lain di luar penelitian seperti harga hingga kualitas produk.